A Pilot Study of Determinants of Ongoing Participation in EnhanceFitness. Issue 4 (October 2015) - Gillette, David B.; Petrescu-Prahova, Miruna; Herting, Jerald R.; Belza, Basia
<x xml:space="preserve">Abstract</x> Background and Purpose: Physical activity has many benefits for older adults, but adherence is often low. The purposes of this study were to (1) identify motivators and barriers for participation in EnhanceFitness (EF), a group-based exercise program; and (2) quantitatively examine the association between motivators, barriers and individual characteristics, and ongoing participation in the program. Methods: This was a prospective, cross-sectional study. We mailed a pilot, investigator-developed survey to assess motivators and barriers to exercising to 340 adults who started a new EF class, regardless of their attendance rate. We precoded surveys on the basis of class attendance, with former participants defined as having no attendance a month or more before a 4-month fitness check. Results: Of the 241 respondents (71% response rate), 61 (25%) were precoded as former participants and 180 (75%) as current participants. The mean age of respondents was 71 years and they were predominately female (89%). More than half of respondents were whites (58%), and almost half were married (46%). Former participants reported lower total motivation scores than current participants (P < .01) and had a significantly higher mean total barrier score (P < .001). The effects of 5 barriers ("Class was too hard, " "Class was too easy, " "I don't like to exercise, " "Personal illness, " and "Exercise caused pain") and 2 motivators ("I want to exercise" and "I plan exercise as part of my day") were significantly different between current and former participants. Discrete event history models show that dropout was related positively to ethnicity (whites were more likely to drop out) and health-related barriers. Discussion: In newly formed EF classes, participants who drop out report more program, psychosocial, and health barriers, and fewer program and psychosocial motivators. Total barrier score and health barriers significantly predict a participant's dropping out, and white ethnicity is associated with a higher likelihood of dropping out. Conclusions: Employing strategies that address health barriers to participation could improve attendance rates for group-based exercise programs.